Improving the technology of aeration of the food system of mousse at horeca enterprises - Dzyuba, Nadya; Oliinyk, Mariia; Kalugina, Iryna; Poplavska, Svitlana; Bortnykov, Yevhenii; Zakharova, Svitlana (Eastern-European Journal of Enterprise Technologies, 2023)
There is an interest in sweet dishes such as aerated desserts, which are gaining popularity among consumers. Raw materials of plant origin, used in the technology of aerated products, are intended mainly to improve their quality characteristics. Especially for enrichment with protein substances, micro and macro elements, vitamins, as well as to obtain a product rich in dietary fiber content. In the segment of aerated dessert products, a distinctive feature of which is the multistage of the production process and the need to use special equipment, technologies involve the use of foam and structure-forming food additives. For the formation of a whipped and stable structure, as well as the addition of surfactants that can cover the surfaces of bubbles and prevent their coalescence, food additives of various origins are used. Therefore, it is relevant to investigate the foaming ability and stability of aerated desserts and improve the technological parameters of the processes or foam structures of desserts. It is necessary to take into account the structural and mechanical properties of aerated dessert products, which are the main characteristics of the quality of aerated desserts. Thus, it is relevant to devise technologies for aerated desserts and food additives in their composition, which will serve as a stabilizing agent, as well as a dietary supplement. A recipe for aerated dessert – mousse based on fermented milk cheese with the introduction of a complex additive into the recipe – was developed. The optimal amount of food additive in the composition of aerated dessert, which is 3 % of the recipe composition, has been established, which will ensure the stability of the food system of aerated products, in particular mousses. The influence of the additive on the structural and mechanical properties of the food system of dessert has been investigated. The experimental data could be used for improving technologies for the production of aerated desserts.